2019
DOI: 10.22159/ajpcr.2019.v12i3.29651
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic Activity of Rodent Tuber Mutant Plant (Typhonium Flagelliforme Lodd.) Against to McF-7 Breast Cancer Cell Line

Abstract: Objective: The objective of this study was to determine the new bioactive compounds through gas chromatography–mass spectrometry analysis and the cytotoxic activity of two rodent tuber mutant plants against breast cancer cells (MCF-7). Methods: The bioactive compounds in rodent tuber mutant plants were successfully increased by somaclonal variation using gamma rays irradiation technique. Further, the cytotoxicity activity of rodent tuber mutant plants was tested on breast cancer cell line (MCF-7) perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…29 It has been demonstrated that four compounds, oleic acid, palmitic acid, linoleoyl chloride, and hexadecanoic acid, methyl ester, have potential anticancer activity. Two of these four compounds, oleic acid and palmitic acid, have the most anticancer activity, as reported by Liu et al 27 and Sianipar et al, 30 respectively. Table 3 summarizes that oleic acid and palmitic acid have higher concentrations in WGO than in WGP.…”
Section: ■ Discussionmentioning
confidence: 55%
“…29 It has been demonstrated that four compounds, oleic acid, palmitic acid, linoleoyl chloride, and hexadecanoic acid, methyl ester, have potential anticancer activity. Two of these four compounds, oleic acid and palmitic acid, have the most anticancer activity, as reported by Liu et al 27 and Sianipar et al, 30 respectively. Table 3 summarizes that oleic acid and palmitic acid have higher concentrations in WGO than in WGP.…”
Section: ■ Discussionmentioning
confidence: 55%
“…35 Meanwhile, octadecanoic acid, methyl hexadecanoate, hexadecanoic acid, and octadec-9-enoic acid were believed to have potential as anticancer. 36 Based on this study, the anticancer activities could be contributed from the detected chemical compounds in the extracts derived from dark fermentation as analyzed by GC-MS. Searching other potency as antibacterial agent was also conducted by testing the extracts against S. aureus as gram-positive bacteria and E. coli as gram-negative bacteria. Similar with antioxidant potency, extract from fermentation under light condition showed better activity against S. aureus compared to dark condition, although only slight differences in viability were observed (at the concentration of 250, 125 and 31.25 µg/mL).…”
Section: Bioactivitiesmentioning
confidence: 94%
“…In comparison, the ethanol extract has an IC50 value of 1.60 µg/mL [9]. This indicated that the cytotoxic activity of T. flagelliforme mutant extract was three times more effective than wild-type extract, with an IC50 value of 19.11 µg/mL [8].…”
Section: Introductionmentioning
confidence: 95%
“…T. flagelliforme mutant plant received Plant Variety Protection by the Indonesian Ministry of Agriculture in 2020. T. flagelliforme mutant plant has been shown to have bioactive compounds, and its potential as an anticancer agent has increased [6][7][8]. The ethyl acetate fraction of the superior T. flagelliforme mutant has potential as an anticancer with an IC50 value of 1.09 µg/mL.…”
Section: Introductionmentioning
confidence: 99%